Genome-Wide Linkage Study of Retinal Vessel Diameters in the Beaver Dam Eye Study - Chao Xing; Barbara E.K. Klein; Ronald Klein; Gyungah Jun; Kristine E. Lee; Sudha K. Iyengar (2006)
Retinal vessels can be observed noninvasively and provide a window to microvascular systems elsewhere in the body. Generalized retinal arteriolar narrowing can represent structural changes resulting from persistent high blood pressure. However, data from recent studies also suggest that generalized retinal arteriolar narrowing might precede hypertension and contribute to its pathogenesis. To determine whether vessel diameters in the eye are genetically determined, we conducted a genome-wide linkage scan on retinal vessel diameters (central retinal artery equivalent and central retinal vein equivalent) using data from the Beaver Dam Eye Study. There were 7 regions on 5 chromosomes (3q28, 5q35, 7q21, 7q32, 11q14, 11q24, and 17q11) showing linkage signals at the nominal multipoint significance level of 0.01 for either covariate-unadjusted or -adjusted central retinal artery equivalent; there were 7 regions on 6 chromosomes (1p36, 6p25, 6q14, 8q21, 11p15, 13q34, and 14q21) showing linkage signals at the nominal multipoint significance level of 0.01 for either covariate-unadjusted or -adjusted central retinal vein equivalent. The linkage results for retinal vessel diameters indicate genetic contributions that remain significant even after adjusting for hypertension and other covariates. In summary, we provide evidence demonstrating that genetic factors independent of hypertension affect retinal vessel diameters.